Avaliação da capacidade funcional e da função pulmonar em crianças e adolescentes com anemia falciforme - Silva, Jonathan Luiz da (2019)
Introduction: Sickle cell anemia (SCA) is a haematological disease caused by defects in hemoglobin structure, such as complications caused by diseases that may cause functional capacity limitation and quality of life impairment. Objective: To evaluate the functional capacity, pulmonary function and quality of life of children and adolescents with AF.Method: Cross-sectional study of children and adolescents aged 6 to 18 years with the SCA genotype HbS-S (group-SCA) matched for age and sex. to their feeding peers (Control Group - CG).Employees underwent pulmonary function test, PedsQl quality of life questionnaire, muscle respiratory strength (FMR), elevation test and five-repetition test (TLS-5rep) and after the modified test shuttle(STM).Results: Forty-eight G-SCA volunteers and 48 CG volunteers were selected, with a mean age of 13 ± 3 years, and a G-SCA pulmonary function was lower compared to CG FVC (previous%) 92 ± 15 vs 104 ± 15, FEV1 (previous%): 83 ± 15 vs 101 ± 13, FEV1 / FVC: 84 ± 8 vs 90 ± 6, FEF25-75% (previous%): 82 ± 22 vs: 108 ± 22 and PEF (previous%) 72 ± 22 vs CG: 92 ± 18, respectively, p <0.05. In quality of life or G-SCA, the lowest scores are evaluated in all domains of PedsQl when compared to CG: health 66 (59-74) vs 94 (79-97), feelings: 65 (50-80) vs 75 (60-89), social: 80 (66-94) vs 95 (81-100) and school 50 (40-70) vs 87 (74-91) p <0.05 respectively, showing the worst quality of life. When assessing TLS-5 functional capacity or execution time, the G-SCA was higher in relation to controls 8 (7.4-8.9 sec) vs 7 (7.0-8.08 sec) p <0.001 and total distance traveled in meters and% of predicted for STM was shorter than for healthy peers, DTP: 576 (515-672m) vs 1010 (887-1219m) and previous% 58 (50-54) vs 101 (89 -111)) p <0.001 Conclusion: Children and adolescents with SCA have functional capacity and reduced quality of life when compared to their control pairs.